Electroactive polyamide modified carbon paste electrode for the determination of ascorbic acid. Issue 13 (20th October 2016) - Yeh, Lu-Chen; Huang, Tsao-Cheng; Lin, Yen-Jen; Lai, Guan-Hui; Yang, Ta-I; Lo, An-Ya; Yeh, Jui-Ming
ABSTRACTS: Construction electroactive polyamide (EPA) with aniline-pentamer-based in the main chain has been modified on the surface of carbon paste electrode (CPE) for detecting ascorbic acid (AA). Fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy studies confirm the well-defined molecular structure of the oligoaniline and EPA. Further, the in situ chemical oxidation of EPA was monitored by UV-Visible absorption spectrum. The electroactivity of the EPA was evaluated by performing electrochemical cyclic voltammetry study. The sensing response studies have revealed that this EPA-modified CPE electrode can detect AA in the range of 0.05–0.7 mM with detection limit of 0.005 mM and sensitivity of 1.5 × 10 –5 AmM –1 . Besides, this EPA-modified CPE electrode shows a minimal relative standard deviation of 1.73%.